2015
DOI: 10.1080/00140139.2015.1038306
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the realism of digital human manikins used for simulation in ergonomics

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. AbstractIn this study, the accuracy of the joint centers of the manikins generated by RAMSIS and Human Builder (HB), two digital human modeling systems widely used in industry for virtual ergonomics simulation, was investigated. Eighteen variously sized females and males were generated from external anthropometric dimensions and six joint centers (knee, hip an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In the present work, a surface matching error lower than 10 mm on average was obtained for all four tested methods. This is slightly higher than the mean error of reconstruction of the external envelope obtained from biplanar X-rays of 5 mm (Nérot et al, 2015b), suggesting that a good surface fit could be obtained using a reduced number of PCs from an existing sample datasets. Table 5 gives the Pearson correlation coefficients between the prediction errors of internal points in the anterior-posterior direction (x) and those of external body surface as well as their correlations with different individual characteristics, such as body height, weight, age, T4-T12 kyphosis and L1-L5 lordosis angles.…”
Section: Tablementioning
confidence: 83%
See 1 more Smart Citation
“…In the present work, a surface matching error lower than 10 mm on average was obtained for all four tested methods. This is slightly higher than the mean error of reconstruction of the external envelope obtained from biplanar X-rays of 5 mm (Nérot et al, 2015b), suggesting that a good surface fit could be obtained using a reduced number of PCs from an existing sample datasets. Table 5 gives the Pearson correlation coefficients between the prediction errors of internal points in the anterior-posterior direction (x) and those of external body surface as well as their correlations with different individual characteristics, such as body height, weight, age, T4-T12 kyphosis and L1-L5 lordosis angles.…”
Section: Tablementioning
confidence: 83%
“…3D reconstructions of body envelope and skeleton (including pelvis and spine) were performed from the participants' biplanar X-rays (Mitton et al, 2006, Humbert et al, 2009. The envelope reconstruction method already described in our previous work (Nérot et al, 2015b), consists of deforming a template of the human body envelope to match the visible skin contours on the X-rays ( Fig. 1a).…”
Section: Datamentioning
confidence: 99%
“…By applying the DHM to scan transformation, DHM joint centers are estimated in the scan position. In a recent study [16], the location of the joint centers of RAMSIS and Human Builder DHMs generated using a few anthropometric dimensions was compared with those obtained from two perpendicular x-ray images. Results showed that both RAMSIS and HB could correctly reproduce external anthropometric dimensions, while the estimation of internal joint centers location presented an average error of 27.6mm for HB and 38.3mm for RAMSIS.…”
Section: Discussion and Future Workmentioning
confidence: 99%